(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background: Endotracheal intubation is gold standard of general anesthesia. various oral, Maxillofacial, Dental surgeries are carried out in high-risk patients having chances of difficult intubation. If we give sedation or general anesthesia, we can be trapped in critical airway accidents. Aims & objectives: To access & compare efficacy of anatomical landmark guided/ Ultrasound guided superior laryngeal nerve block associated with topical Anesthesia & transtracheal block for awake blind nasal intubation.Method: Group A: Anatomical landmark guided superior laryngeal nerve block given(n=30) Group B: ultrasound guided superior laryngeal nerve block(n=30) In both groups topical Anesthesia & transtracheal block for awake blind nasal intubation was given.Results: upper airway block provide clinical ease to facilitate blind nasal awake intubation. ultrasound guided block has less adverse reactions. Conclusion: Both methods provide good quality of Endotracheal intubation, but ultrasound guided block is more efficient & scientific method to block superior laryngeal nerve for awake nasal intubation.